2018
DOI: 10.1021/acssuschemeng.8b02697
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fibers Derived from Fractionated–Solvated Lignin Precursors for Enhanced Mechanical Performance

Abstract: The sustainable solvent system acetic acid + water was used to simultaneously fractionate, solvate, and clean a softwood Kraft lignin for conversion to carbon fibers. By exploiting the novel liquid− liquid equilibrium (LLE) phase behavior exhibited by this pseudoternary system, three fractionated−solvated lignin precursors (FSLPs) of increasing molecular weight (7200, 13 800, and 28 600) were obtained via the continuous Aqueous Lignin Purification using Hot Acids (ALPHA) process. It is noteworthy that all thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 33 publications
4
95
0
Order By: Relevance
“…Water soluble lignin-based CFs had a lower yet still practically viable elastic modulus of 16 GPa, similar to the modulus for pure kraft lignin-derived CFs (15.7 GPa). Despite using lignin as a sustainable feedstock in this process, it should be noted that all of the PAN-derived CF reactions emit toxic hydrogen cyanide gas, which is a drawback to this approach [42].…”
Section: Lignin-derived Carbon Fibersmentioning
confidence: 99%
“…Water soluble lignin-based CFs had a lower yet still practically viable elastic modulus of 16 GPa, similar to the modulus for pure kraft lignin-derived CFs (15.7 GPa). Despite using lignin as a sustainable feedstock in this process, it should be noted that all of the PAN-derived CF reactions emit toxic hydrogen cyanide gas, which is a drawback to this approach [42].…”
Section: Lignin-derived Carbon Fibersmentioning
confidence: 99%
“…In addition, PVA displays strong interactions with lignin, [19] and as shown further, can even exhibit partial miscibility with lignin. [2,6,18] In contrast to previous related investigations, we use unmodified lignin to keep the cost low, and 2-propanol as coagulating medium to keep the process simple and environmentally friendly. We demonstrate the fabrication of lignin-based fibers via a continuous wet-spinning method using nonhazardous solvents (dimethyl sulfoxide (DMSO) and 2-propanol) at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[2,8,10] In addition, it leads to carbon fiber properties that compare or exceed the properties of fibers made from other types of lignin. [2,6,18] In contrast to previous related investigations, we use unmodified lignin to keep the cost low, and 2-propanol as coagulating medium to keep the process simple and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al (2018) isolated and fractionated softwood kraft lignin from black liquor using the ALPHA process, which uses liquid-liquid equilibrium present in an acetic acid-water solution. 52 This method allows for separating lignin by molecular weight through adjusting the ratio of acetic acid to water. The researchers used this feature to produce lignin-derived CFs from three samples with different molecular weights, and they found that tensile strength and modulus increase as molecular weight increases.…”
Section: Graphitization Of Fractionated Ligninmentioning
confidence: 99%